Accuracy of internet images of ligamentous knee injuries. Issue 1 (2nd January 2019) - DeFroda, Steven F.; Bokshan, Steven L.; Vutescu, Emil Stefan; Sullivan, Kayleigh; Owens, Brett D.
ABSTRACT: Background : The internet is an easily accessible resource for both providers and patients. Despite this, the internet is not peer reviewed, leaving searches subject to inaccuracies, especially with regards to medical information. The purpose of this study was to review internet images of anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), medial collateral ligament (MCL), and lateral collateral ligament (LCL) tears using two popular search engines: Google and Bing. Methods : A search query was performed on both Google and Bing for the following terms: 'ACL tear', 'PCL tear', 'MCL tear' and 'LCL tear'. The first 100 images of each individual search were analyzed by three independent orthopedists. Results : The inter-rater reliability was very good for PCL tear on Bing (Cronbach's alpha = 0.89) and excellent (Cronbach's alpha > 0.9) for the remainder of the search queries. When comparing Google to Bing, the only significant difference occurred in the ACL group, with Bing returning a significantly greater number of correct images 60%, 95% CI: 53.2 – 66.7%) compared to Google (45% correct, 95% CI: 38.1–51.8%), p = 0.034. With regards to the other ligaments Bing was more accurate than Google for PCL (39% versus 38%), and LCL (32% to 30%). Both sites were 48% accurate for MCL tear. Conclusion : Ultimately, our study revealed that physicians should take an active role in making high quality, easy to understand medical resources and anatomic diagrams available to their patients to avoid confusion and enhance understanding when querying the internet for additional information regarding their condition.